Characteristic properties of the three-half-turn-antenna-driven RF discharge in the Uragan-3M torsatron - Chechkin, V.V.; Grigor’eva, L.I.; Grekov, D.L.; Pavlichenko, R.O.; Lozin, A.V.; Kasilov, A.A.; Beletskii, A.A.; Kozulya, M.M.; Kulaga, A.Ye.; Zamanov, N.V.; Tarasov, I.K.; Mironov, Yu.K.; et al. (Вопросы атомной науки и техники, 2014)
In the λ = 3 Uragan-3M torsatron hydrogen plasma is heated by RF fields in the Ålfven range of frequencies (ω≤ωсi). Plasma with the mean density ‾ne units of 10¹² сm⁻³ is produced by the frame antenna and used as an initial plasma (“target”) to produce and heat a denser plasma (up to ‾ne ~ 10¹³ сm⁻³) by means of the shorter wavelength three-half-turn antenna with azimuthal currents. Characteristics of the three-half-turn-antenna-driven discharge are studied experimentally depending on the RF power fed to the antenna and initial plasma parameters. В трехзаходном торсатроне Ураган-3М водородная плазма создается и нагревается ВЧ-полями в области альфвеновских частот (ω≤ωсi). Плазма со средней плотностью ‾ne единицы 10¹² см⁻³ создается рамочной антенной и используется как исходная для получения и нагрева более плотной плазмы (до ‾ne ~ 10¹³ см⁻³) с помощью более коротковолновой трехполувитковой антенны с азимутальными токами. Экспериментально исследуются характеристики ВЧ-разряда, поддерживаемого трехполувитковой антенной, в зависимости от ВЧ-мощности, подводимой к антенне, и параметров исходной плазмы. У трьохзаходному торсатроні Ураган-3М воднева плазма створюється і гріється ВЧ-полями в області альфвенівських частот (ω≤ωсi). Плазма з середньою щільністю ‾ne одиниці 10¹² см⁻³ створюється рамковою антеною і використовується як початкова для одержання та нагріву щільнішої плазми (до ‾ne ~ 10¹³ см⁻³) за допомогою більш короткохвильової трьохнапіввиткової антени з азимутальними струмами. Експериментально досліджуються характеристики ВЧ-розряду, який підтримується трьохнапіввитковою антеною, в залежності від ВЧ-потужності, що підводиться до антени, та параметрів початкової плазми.